Determinants of Child Marriage Using Ecological Theory: A Literature Review - Putri, Nike Dwi; Achmad, Harun; Pulubuhu, Dwia Aries Tina (Budapest International Research and Critics University, 2021)
Indonesia is one of the ten countries with the highest prevalence of child marriage in the world. Efforts to prevent the practice of child marriage can be done through intervention on the determinants of child marriage. This article aims to examine and explain the factors that influence child marriage referring to ecological theory. The research method used is a literature review. Article searches were conducted on online journal databases found in Pubmed, Proquest, ScienceDirect, and Willey Online Library with the keyword